HUBUNGAN IMPLEMENTASI ISO 9001 DAN KEGIATAN TEACHING FACTORY DENGAN MUTU PEMBELAJARAN PRODUKTIF DI SEKOLAH MENENGAH KEJURUAN SWASTA DI KABUPATEN KUDUS - Arif Zaenal Mubarok; Nurkolis; Ngasbun Egar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The quality of learning is the key to achieving the quality of educational output, namely qualified graduates according to the minimum standards set. Strategic steps in an effort to improve the quality of productive learning can be carried out with a commitment to implementing ISO 9001 and teaching factory learning effectively. Research objectives: 1) to determine the relationship between the implementation of ISO 9001 and the quality of productive learning, 2) to determine the relationship between teaching factory activities and the quality of productive learning, and 3) to determine the relationship between the simultaneous implementation of ISO 9001 and teaching factory activities and the quality of productive learning at private vocational schools in the district. Holy. This study uses a quantitative method with a correlational approach. The population in this study was a private vocational school teacher in the field of engineering technology in Kudus Regency with a total of 88 people. Data collection techniques using a questionnaire. The results of the study: 1) there is a relationship between the implementation of ISO 9001 and the quality of productive learning at 95.0%, the first hypothesis is proven, 2) there is a relationship between teaching factory and the quality of productive learning at 95.0%, the second hypothesis is proven, 3) there is a relationship between implementation ISO 9001 and teaching factory activities together on the quality of productive learning in Private Vocational Schools in Kudus Regency by 97.6%, the third hypothesis is proven. Conclusion: 1) the implementation of ISO 9001 has a positive and significant relationship to the quality of productive learning in Private Vocational High Schools in Kudus Regency, so the first hypothesis is accepted (significance value 0.000 <0.05), 2) teaching factory activities have a positive and significant relationship with the quality of productive learning Private Vocational High Schools in Kudus District, so the second hypothesis is accepted (significance value 0.000 <0.05), 3) implementation of ISO 9001, and teaching factory activities together have a positive and significant relationship to the quality of productive learning of Private Vocational High Schools in the District Kudus, so the third hypothesis is accepted (significant value of F change 0.000 <0.05). Suggestions from researchers: 1) productive subject teachers improve the quality of productive learning, especially in the dimensions of learning management strategies, 2) productive subject teachers improve skills in teaching factory activities especially in the teacher dimension, and 3) school principals are highly committed to implementing ISO 9001, especially on the organizational context dimension.